PENGEMBANGAN MODUL TEKS EKSPLANASI BERMUATAN PROFIL PELAJAR PANCASILA DAN AKHLAK ISLAM SMP KELAS VII BERBASIS FLIPBOOK - Putri Utami Dewi; Khaerunnisa (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
This research was conducted against a background of problems, namely the limited digital teaching materials, especially in the Indonesian subject of explanatory text. In Indonesian language lessons, especially in explanatory text material, the teacher does not use other innovative teaching materials. In addition, the minimal availability of teaching materials makes learning less effective. The low literacy of students also makes their knowledge limited in developing topics. The existence of the Covid-19 pandemic has an impact on learning. This requires teachers to innovate in using technology based teaching material for distance learning. The purpose of this research is to develop digital teaching materials in the form of modules in explanatory text material that will help students learn independently. Data collection techniques used by researchers, namely observation, interviews, questionnaires, needs analysis and validation of material experts and media experts. This type of R&D research method uses the ADDIE model (Analaysis, Design, Development, Implementation, Evaluation). The research was conducted at Darussalam Integrated Junior High School and PGRI 336 Junior High School. The Number of subjects consisted of 60 students. The results of this study get a very decent category which can be seen from the percentage. Material experts are 86% in the very valid category, media experts are 91% in the very valid category, large class trials are 88% in the very practical category, and 96% teacher trials are in the very practical category. Keywords: Module, Text Explanation, Flipbook